2016
DOI: 10.1016/j.autneu.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects on hemodynamic variables and echocardiographic parameters after a stellate ganglion block in 15 healthy volunteers

Abstract: Even with our methods we could not prevent the simultaneous occurrence of a partial parasympatholytic effect. For this reason, the SGB has only minor hemodynamic effects, which is desirable as it enhances the safety of the SGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 112 publications
2
42
0
Order By: Relevance
“…The role of stellate ganglion block is well known in patients with chronic pain because of the reduction in sympathetic tone, and prevention of central sensitization helping to have normal somatic sensation [20,21]. De La Vega Costa et al reported that SGB has minor effects on the hemodynamic status [22], which is similar to our study. In the current study we did not find major hemodynamic consequences in patients after performing SGB.…”
Section: Discussionsupporting
confidence: 90%
“…The role of stellate ganglion block is well known in patients with chronic pain because of the reduction in sympathetic tone, and prevention of central sensitization helping to have normal somatic sensation [20,21]. De La Vega Costa et al reported that SGB has minor effects on the hemodynamic status [22], which is similar to our study. In the current study we did not find major hemodynamic consequences in patients after performing SGB.…”
Section: Discussionsupporting
confidence: 90%
“…Beside the action on sodium ion channels, additional molecular mechanisms in NT have been revealed. Local anesthetics induce Gq‐protein‐complex mediated intracellular anti‐inflammatory mechanisms deactivate overactive granulocytes, inhibit the signaling of human N‐methyl‐D‐aspartate (NMDA) receptors, and affect the synthesis and release of inflammatory mediators as eicosanoids, histamine, prostaglandins, and cytokines …”
Section: Discussionmentioning
confidence: 99%
“…Local anesthetics also induce vasodilatation, reduce a pathologically increased capillary permeability, have antimicrobial properties, and exhibit a sympatholytic effect …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations